Real-world long-term outcomes in individuals at clinical risk for psychosis: The case for extending duration of care. (November 2020) - Fusar-Poli, Paolo; De Micheli, Andrea; Signorini, Lorenzo; Baldwin, Helen; de Pablo, Gonzalo Salazar; McGuire, Philip
Abstract: Background: Most services for individuals at Clinical High Risk for Psychosis (CHR-P) provide short-term clinical care. This study determines the real-world and long-term clinical outcomes beyond transition to psychosis in a large cohort of CHR-P individuals. Method: Retrospective RECORD-compliant real-world Electronic Health Records (EHR) cohort study in secondary mental health care (the South London and the Maudsley -SLaM- NHS Foundation Trust). All CHR-P patients accessing the CHR-P service at SLaM in the period 2001–2018 were included. Main outcomes were long-term cumulative risk of first: (i) developing an ICD-10 psychotic disorder (primary outcome), receiving a treatment with (iia) antipsychotic medication, (iib) benzodiazepines, (iic) other psychotropic medications, (iid) psychotherapy, receiving an (iiia) informal or (iiib) compulsory admission into a mental health hospital, and the time to these events; (iiic) number of days spent in hospital and (iv) cumulative risk of death for any reason and age/gender Standardised Mortality Ratio (SMR). Data were extracted from the EHR and analysed with Kaplan Meier failure functions, Cox and zero-inflated negative binomial regressions. Findings: 600 CHR-P patients (80.43% Attenuated Psychotic Symptoms, APS; 18.06%, Brief and Limited Intermittent Psychotic Symptoms, BLIPS, 1.51% Genetic Risk and Deterioration Syndrome) were included (mean age 22.63 years, range 13–36; 55.33% males; 46.44% white, mean duration of untreated attenuated psychotic symptoms 676.32 days, 1105.40 SD). The cumulative risk to first psychosis was 0.365 (95%CI 0.302–0.437) at 11 years; first antipsychotic 0.777 (95%CI 0.702–0.844) at 9 years; first benzodiazepine 0.259 (95%CI 0.183–0.359) at 12 years; first other types of medications 0.630 (95%CI 0.538–0.772) at 9 years; first psychotherapy 0.814 (95%CI 0.764–0.859) at 9 years; first informal admission 0.378 (95%CI 0.249–0.546) at 12 years; first compulsory admission 0.251 (95%CI 0.175–0.352) at 12 years; those admitted spent on average 94.84 (SD=169.94) days in hospital; the cumulative risk of death for any reason was 0.036 (95%CI 0.012–0.103) at 9 years, with an SMR of 3.9 (95%CI 1.20–6.6). Compared to APS, BLIPS had a higher risk of developing psychosis, being admitted compulsorily into hospital, receiving antipsychotics and benzodiazepines and lower probability of receiving psychotherapy. Other prognostic factors of long-term outcomes included age, symptoms severity, duration of untreated attenuated psychotic symptoms, ethnicity and employment status. Interpretation: Duration of care provided by CHR-P services should be expanded to address long-term real-world outcomes. Funding: This study was supported by the King's College London Confidence in Concept award from the Medical Research Council (MRC) (MC_PC_16048) to PF-P. GSP is supported by the Alicia Koplowitz Foundation. HB is supported by a National Institute for Health Research Maudsley Biomedical Research Centre studentship.